Metapsicopatologia da psiquiatria: uma reflexão sobre o dualismo epistemológico da psiquiatria clínica entre a organogênese e a psicogênese dos transtornos mentais - Martinez, José Roberto Barcos (2006)
This doctoral thesis intends to analyze the main concepts of mental disease and the problematic relation between the organicism and the psychodinamism throughout the history of the psychopathologic ideas that came to constitute the scientific clinical psychiatry, from Philippe Pinel, in the beginning of XIX century, until the chaos of the no theoretical pretense descriptive of the official nosography of the end of XX century and beginning of XXI century (I.C.D.-10). The epistemologic conflict between the psychogenic and organogenic doctrines had resulted in many frustrated attempts of solution. The hermeneuticsynthetic psychopathology of Carl Gustav the Jung (1875-1961) and the phenomenonstructural psychopathology of Eugène Minkowski (1885-1972) stand out among the most promising proposals of XX century. The basic concepts of these authors keep an essential similarity, besides belonging to schools have different thoughts. However, their theorization go in parallel thinking about a psychopathologic formularization psychorganodinamic that is similar in its most essential principles. The antimechanist solution, anti-atomicist and antireductionist, of both, remind the current biological psychiatry that the desired and necessary consensual psychiatric theory will not do without a Metapsychopatology of the psychiatry that consider the irreducible biopsychosocial complexity of the normal or pathological human being. And, neither psychiatry will gain a satisfactory nosographic formularization while they don t reveal the mysteries of the complex etiology of mental disorders.